A hybrid service metadata clustering methodology in the digital ecosystems environment - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (IEEE Computer Society, 2009)
Digital Ecosystems (DE) is an open, loosely coupled, domain clustered, demand-driven, self-organizing and agent-based environment, in which each species is proactive and responsive for its own benefit and profit. Species in DE can play dual roles, which are service requester (client) that needs services and service provider (server) that provides services. A service provider enters DE by publishing a service in the service factory, which will be clustered by domain-specific ontologies provided by DE. Two issues could exist here. The first is that the pre-existing service metadata cannot be easily clustered because of the lack of technological support. To solve this issue, an automatic service metadata clustering method is desired. However, this could educe the second issue the outcome of the method could not agree with service providers perception. To solve the two issues, in this paper, we present an ontology-based metadata clustering methodology, with a complement of a service provider-oriented metadata clustering approach. The information regarding the prototype implementation and the evaluation of this methodology is revealed in the final section.